TECHNOLOGY OF PROCESSING OF MOLYBDENUM CONTAINING DEAD CATALYSTS - O. S. Komarov; V. I. Volosatikov; D. O. Komarov; I. B. Provorova (Литьë и металлургия)
Efficiency of hydrometallurgical leaching of molybdenum with alkali, soda and ammonia in course of processing of spent catalysts was considered.